Hepatitis E during Tocilizumab Therapy in a Patient with Rheumatoid Arthritis: Case Report and Literature Review - Hidekazu Ikeuchi; Kana Koinuma; Masao Nakasatomi; Toru Sakairi; Yoriaki Kaneko; Akito Maeshima; Yuichi Yamazaki; Hiroaki Okamoto; Toshihide Mimura; Satoshi Mochida; Yoshihisa Nojima; Keiju Hiromura (Case Reports in Rheumatology)
Hepatitis E is an acute self-limiting disease caused by hepatitis E virus (HEV). Recent reports show that HEV can induce chronic hepatitis or be reactivated in immunocompromised hosts. We report a 63-year-old woman with rheumatoid arthritis (RA) who developed hepatitis E during treatment with tocilizumab. Analysis of serially stocked serum samples confirmed that hepatitis was caused by primary infection with HEV and not by viral reactivation. Her liver function improved after discontinuing tocilizumab and remained within the normal range without reactivation of HEV for >5 years after restarting tocilizumab. We also reviewed the published cases of hepatitis E that developed during RA treatment.